Glimpses of hungryland; or, California sketches. Comprising sentimental and humorous sketches, poems, etc., a journey to California and back again, by land and water ... - Walker, W. S. (Cloverdale, Cal., Reveille publishing house, 1880)
W. S. Walker left Mason City, Illinois, for New New York City and his first trip to California (via the Isthmus) in 1864. Glimpses of hungryland (1880) describes his stay in the West: a series of odd jobs in Sonoma County, gold prospecting at Park's Bar on the Yuba River, and a revival camp meeting near Healdsburg. In 1879, he takes his family from Omaha to California by rail on the "Emigrant Train" and gives a tourist's account of San Francisco.
Also available in digital form on the Library of Congress Web site.
Keywords: California -- Description and travel; Overland journeys to the Pacific; Mines and mineral resources -- California; Religion and ethics -- California